Tradisi Grindadrap: Pelanggaran Hukum Internasional Berkedok Indigenous People? - Tutuarima, Meylin; Anwar, Arman; Wattimena, J.A.Y (Faculty of Law, Universitas Jambi, 2023)
Dolphins are protected animals, but dolphin hunting is still found in several countries, one of which is in the Faroe Islands, Denmark. The tradition of hunting dolphins in this country is part of the rights of indigenous peoples called grindadrap. The grindadrap tradition can be categorized as Aboriginal Subsitence Whaling (ASW), where this activity is an act of hunting whales and dolphins for the benefit of culture or traditions that exist in a country. However, this activity is a violation of the International Convention for the Regulation of Whaling (ICRW). This article uses normative legal research and sources of written legal material as its analysis. The results showed that this paradigm shift in the grindadrap tradition has deviated from its main goal, namely as part of meeting people's food needs which are now turning into commercial needs and sports events so that there is a violation of law in the realm of international law. As one of the states parties to the ICRW, Denmark has an obligation to abide by the agreed rules. For this reason, Denmark has a responsibility in solving this violation problem. one of the middle ways to overcome this problem is through the development of conservation-based programs, namely the Conservation Committee Strategic Plan 2016-2026. This effort is more effective relying solely on hunting stops.Â The move was used to arouse the enthusiasm of other countries and urged the commission to develop the International Whaling Commission (IWC) into a capable organization to stop whaling and dolphin poaching.